High Expression of Vimentin is Associated With Progression and a Poor Outcome in Glioblastoma. Issue 5 (May 2018) - Zhao, Jiaxin; Zhang, Liqiu; Dong, Xingli; Liu, Lu; Huo, Linman; Chen, Huirong
Abstract : Glioblastoma multiforme (GBM) has a high recurrence and mortality rate. Because of a poor understanding of the mechanism for this disease, treatment regimens have remained limited. Vimentin, one of the major cytoskeletal proteins, is associated with cellular structure. However, the function of vimentin in GBM is still undefined. In the present study, we investigated the expression level of vimentin in 179 GBM tissues using immunohistochemistry. We found that the vimentin expression level was associated with the time to progression ( P =0.029). A Kaplan-Meier analysis revealed that patients with high vimentin expression had a significantly shorter overall survival ( P =0.0002) and progression-free survival ( P =0.0001) compared with those with low expression. Furthermore, in vitro experiments showed that withaferin-A, a chemical inhibitor of vimentin, could inhibit GBM cell migration and invasion activity when its concentrations were <0.5 μM, and higher concentrations of withaferin-A could decrease the viability of U251and U87 cells significantly. In conclusion, our results indicated that vimentin may play an important role in the progression of GBM.